Therapeutic affordances of online support group use in women with endometriosis - Shoebotham, Amie; Coulson, Neil S. (Journal of Medical Internet Research, 2016)
Background: The Internet has provided women living with endometriosis new opportunities to seek support online. Online support groups may provide a range of therapeutic affordances which may benefit these women. Objective: To examine the presence of therapeutic affordances as perceived by women who use endometriosis online support groups. Methods: Sixty-nine women (aged 19 to 50 years; Mean = 34.2; 65.2% UK; 21.7% USA) participated in an online interview exploring online support group use. Participants had been using online support groups on average 2 years and 4 months (Range = 1 month to 14 years, 9 months). Responses were analysed using inductive thematic analysis. Results: The analysis revealed 4 therapeutic affordances related to online support group use; i) “connection” i.e. the ability to connect in order to support each other, exchange advice, and to try to overcome feelings of loneliness; ii) “exploration” i.e. the ability to look for information, learn and bolster their knowledge; iii) “narration” i.e. the ability to share their experiences, as well as read about the experiences of others; and iv) “self-presentation” i.e. the ability to manage how they present themselves online. The associated outcomes of use were predominantly positive, such as reassurance and improved coping. However, a number of negative aspects were revealed including: concerns about the accuracy of information, arguments between members, over-reliance on the group, becoming upset by negative experiences or good news items and confidentiality of personal information. Conclusions: Our findings support the SCENA model (Self-presentation, Connection, Exploration, Narration and Adaptation) proposed by Merolli et al., (2014) and reveal a range of positive aspects that may benefit members, particularly in relation to reassurance and coping. However, negative aspects need to be addressed in order to maximise the potential benefit of support groups. Some of these can be addressed relatively easily through making privacy policies clearer, including health professionals to moderate content and structuring forums to encourage the sharing of positive stories.